KEBERADAAN BURUNG SEBAGAI ATRAKSI EKOWISATA DI KAWASAN BUMI PERKEMAHAN CEKIK TAMAN NASIONAL BALI BARAT - Made Suaskara, Ida Bagus; Ginantra, I Ketut; Raka Dalem, A. A. Gde (Bumi Lestari, 2012)
study on birds as Ecotourism attractions was conducted on August-September 2006 in Cekik Camping Ground, West Bali National Park, Bali-Indonesia. Explorations method was utilised to find out bird species observed in the field. Indentification of birds species was undertaken based on MacKinon (1993). Their status were determined based on Indonesia Regulation (PPRI) No. 7, 1999. Results of this study indicated that in Cekik area were identified 36 bird species that were included in 20 families. The dominant species were member of the family of Sylviidae (6 species), Nectaridae, Columbidae and Dicruridae (3 species respectively). Three species of birds observed on the site were protected by Indonesia Regulation: Brown-throated Sunbird (Anthreptes malacensis), Olive-backed Sunbird (Nectarinia jugularis) and Green banded Kingfisher (Alcedo euryzonia). Perspective utilization of bird for ecotourist (bird watching) attractions in this area was related to the richness of the birds species, their status, activities and interaction with vegetation or on their habitats. The bird activity which might become ecotourist attractions including: foraging, perching, migration and nesting.
Keywords: bird, ecotourism atraction, Cekik Camping Gound, Bali, bird watching